An in vitro intestinal platform with a self-sustaining oxygen gradient to study the human gut/microbiome interface. (6th November 2019) - Kim, Raehyun; Attayek, Peter J; Wang, Yuli; Furtado, Kathleen L; Tamayo, Rita; Sims, Christopher E; Allbritton, Nancy L
Abstract: An oxygen gradient formed along the length of colonic crypts supports stem-cell proliferation at the normoxic crypt base while supporting obligate anaerobe growth in the anoxic colonic lumen. Primary human colonic epithelial cells derived from human gastrointestinal stem cells were cultured within a device possessing materials of tailored oxygen permeability to produce an oxygen-depleted luminal (0.8% ± 0.1% O2 ) and oxygen-rich basal (11.1% ± 0.5% O2 ) compartment. This oxygen difference created a stable oxygen gradient across the colonic epithelial cells which remained viable and properly polarized. Facultative and obligate anaerobes Lactobacillus rhamnosus, Bifidobacterium adolescentis, and Clostridium difficile grew readily within the luminal compartment. When formed along the length of an in vitro crypt, the oxygen gradient facilitated cell compartmentalization within the crypt by enhancing confinement of the proliferative cells to the crypt base. This platform provides a simple system to create a physiological oxygen gradient across an intestinal mimic while simultaneously supporting anaerobe co-culture.